A physical study of passive fire safety requirement at academic building / Muhamad Faizul Nadlan and Zuraihana Ahmad Zawawi - Nadlan, Muhamad Faizul; Ahmad Zawawi, Zuraihana (2018)
Most fire victims are the result of mistake from others. Besides damage to their belongings and property, some occupants are burned to death for not knowing what to do in the event of fire. Passive fire protection is one of the methods used to protect buildings and people from fire. This is supported by good fire safety management to ensure that fire protection is available at all times, facilitating escape in the event of fire and preventing damage to adjacent buildings. This study presents the condition of passive fire safety requirement at Department of Quantity Surveying Block in UiTM Seri Iskandar, Perak. The methodology for conducting the study involved literature review, data collection and analysis. The process of data collection involved obtaining primary data from the surveys by observation and measure at the selected building case studies.